Methodological Study of Juriscprudence of Professional Zakat in Yusuf al-Qardhawi's Perspective - Mohamad R. Tuli; Sofyan A.P. Kau (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2018)
The purpose of this study was to determine the method, foundation and reasoning of Yusuf al-Qardhawi's law on professional zakat. This research is a library research with data collection methods in the form of quoting, adapting and analyzing using content analysis. The results showed that according to Yusuf al-Qardhawi, ijtihad is a serious effort by exerting all abilities by those who have the authority in order to find answers to religious law through istinbât both done hourly (collective) or fardi (individual) by involving other experts . The results of the ijtihad are based on the maqâsid al-syarî‘ah using the qiyas method. On the basis of this principle Yusuf al-Qardhawi stipulates that in determining the obligatory zakat from the profession does not wait a year. The determination of the law does not stand alone, but is supported by the Qur'anic texts, hadith, and analogies. The aspect of justice in determining the obligation of professional zakat for every Muslim is because zakat is essentially worship related to property. A person who has fulfilled his requirements is required to fulfill it, not solely on the basis of his generosity, but if necessary even under pressure from the authorities.